Isolation and Identificationof Octadecane-3-on Compound From Ethyl Acetate Fraction of Momordica balsamina L. Leaves - Pongoh*, Emma Julien; Rumampuk, Rymond Jusuf; Paat, Vlagia Indira; Rumengan, Stefan Marco; Soputan, Julieta (Jurnal IPA & Pembelajaran IPA, 2024)
Momordica balsamina L. is a wild plant that generally grows in moist soil and gets a lot of sunlight. The leaves and fruit are reported to have various medicinal and nutritional properties. This study aimed to isolate and identify the compounds contained in the ethyl acetate fraction in Momordica balsamina L The isolation stage was carried out by the maceration method and the separation and purification of the compounds using gravity column chromatography methods to obtain isolate fraction F1.6.2 with a sample weight of 2.4 mg. Identification of compounds using proton nuclear magnetic resonance (1H-NMR) and carbon nuclear magnetic resonance (13C-NMR) spectroscopy techniques. The proposed identified compound is octadecan-3-one or 3-octadecanone with the molecular formula C18H36O